An Analysis of the Impact of Open Entry on Price and the Quality of Service in the Airline Industry - Trapani, John M.; Olson, C. Vincent (The Review of Economics and Statistics, 1982)
John M. Trapani, C. Vincent Olson, An Analysis of the Impact of Open Entry on Price and the Quality of Service in the Airline Industry, The Review of Economics and Statistics, Vol. 64, No. 1 (Feb., 1982), pp. 67-76